The national humanization policy and the work of the nursing team (Research, Society and Development, 2022)
The work of the nursing professional has been increasingly intense and marked by physical and psychic exhaustion. With this, it is worth mentioning that these professionals deserve attention focused on their quality of health. From this perspective, the National Humanization Policy emerges as a tool modifying the management, working conditions and quality of care offered to health users. Therefore, this study aims to identify the nursing team's understanding of the National Humanization Policy and how the nursing team works in hospitals after the implementation of the National Humanization Policy. The study is a descriptive-exploratory research, with a qualitative approach, carried out with the nursing team in the Adult Emergency Room and Child Emergency Room units in a Clinical Hospital of the Federal University of Triangulo Mineiro, in the Triangulo Mineiro. The data collected were submitted to the content analysis technique / thematic mode. As a result, it was found that professionals have basic knowledge of the National Humanization Policy, looking only at the patient and that the changes in the work environment were positive. Therefore, it was concluded that strategies are needed to bring the knowledge in its entirety to these professionals, through training and refresher courses.